Intravascular ultrasound analysis of small vessel lesions treated with the sparrow coronary stent system: Results of the CARE II trial. Issue 1 (16th March 2013) - Kume, Teruyoshi; Waseda, Katsuhisa; Koo, Bon‐Kwon; Yock, Paul G.; Botelho, Roberto; Verheye, Stefan; Whitbourn, Robert; Meredith, Ian; Worthley, Stephen; Hai, Koh Tian; Honda, Yasuhiro; Abizaid, Alexandre; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to evaluate the Sparrow sirolimus‐eluting stent (Sparrow‐SES) against the Sparrow bare‐metal stent (Sparrow‐BMS) and conventional balloon‐expandable bare‐metal stent (BMS: Driver/Micro‐Driver® stent, Medtronic Vascular, Santa Rosa, CA). Background The Sparrow® stent (Biosensors International, Singapore) consists of a guide wire‐based, self‐expandable, ultra‐thin nitinol stent. The performance of this device with sirolimus in a fully biodegradable polymer has not been determined. Methods A total of 74 patients were included in this intravascular ultrasound (IVUS) sub‐study of the CARE II trial, which was a prospective, randomized, multicenter trial in the treatment of single de novo native coronary artery lesions in vessels ranging from 2.0 mm to 2.75 mm in diameter (Sparrow‐SES: n = 31, Sparrow‐BMS: n = 22, BMS: n = 21). Results Stent volume index (VI) was significantly increased 8‐month later in Sparrow‐SES and Sparrow‐BMS, but not in BMS (4.0±1.0 to 4.6±1.0 mm3/mm, p<0.0001, 4.0±0.6 to 4.4±0.8 mm3/mm, p<0.05, and 5.2±1.0 to 5.1±0.9 mm3/mm, p=0.421, respectively). % neointimal obstruction in Sparrow‐SES was significantly smaller than those in Sparrow‐BMS and BMS at follow‐up (17.6±9.4 vs. 36.2±13.8 and 39.9±11.1%, p<0.001). Sparrow‐SES showed a mean 15% stent expansion and good suppression of neointimal proliferation, resulting in a significantly lower percentage of change in lumen VI during follow‐up period (Sparrow‐SES: −6.2±16.2%, Sparrow‐BMS: −30.4±11.6%, BMS: −40.4±10.0%, p<0.001). Conclusions The self‐expanding Sparrow‐SES demonstrated chronic stent expansion, good suppression of neointimal proliferation and resulted in a more preserved lumen in stented small vessels compared with the Sparrow‐BMS and conventional balloon expandable BMS. © 2013 Wiley Periodicals, Inc.